Investigation of fragmentation statistics of natural materials in laboratory conditions - Bannikova, I.A; Saveleva, N.V. (Perm Federal Research Centre Journal, 2025)
The results of study of the behavior of natural materials (quartzite, sandstone, andesite) under quasi-static, dynamic loading and low-speed indentation (10-3-103 1/s) are presented. The experimental conditions made it possible to preserve fragmented samples and to analyze the statistics of the preserved fragments by size (mass). During the research, a system of laboratory sieve and an HR202i electronic scales with a measurement error of 0.0001 g were used. The method of processing fragment photographs allowed us to establish the number and mass of fragments on sieves with cell sizes up to 0.063-0.05 mm, not less than 99% of the sample weight and minimize measurement error. The obtained cumulative distributions of fragments by mass N(mf) show a change in the shape of the inflection and a shift of the inflection point toward smaller scales with increasing strain rate. The data analysis reflects the similarity of the statistics of fragmentation according to the power law and asymptotic fracture modes with multiple ruptures obtained according to the brittle fracture scenario. It is shown that specimens fracture occurs according to different scenarios depending on loading conditions and is associated with a change in the rate of transition from one stage of crack appearance (or accumulation of stress states, defective structure) to another (crack formation and complete fragmentation). It has been found that the formation of fragments is of an “automodel” nature.